Sex-related differences in retinal function in Wistar rats: implications for toxicity and safety studies - Tyszkiewicz, Cheryl; Hwang, Seo-Kyoung; Manickam, Balasubramanian; Jakubczak, Ben; Walters, Karen M.; Bolt, Michael W.; Santos, Rosemary; Liu, Chang-Ning (Frontiers in Toxicology, 2023)
Introduction: Wistar Han rats are a preferred strain of rodents for general toxicology and safety pharmacology studies in drug development. In some of these studies, visual functional tests that assess for retinal toxicity are included as an endpoint. Although the influence of gender on human retinal function has been documented for more than 6 decades, preclinically it is still uncertain if there are differences or deficits in retinal function between male and female Wistar Han rats. Methods: In this study, sex-related differences in the retinal function were quantified by analyzing the incidence of spontaneous electroretinography (ERG) deficits in 7-9-week-old (n=52 males and 51 females) and 21-23-week-old Wistar Han rats (n=48 males and 51 females). Optokinetic tracking response, brainstem auditory evoked potential, ultrasonic vacuolization and histology were tested in a subset of animals to investigate the compensation mechanisms of spontaneous blindness. Results/Discussion: Absence of ERG responses to flash stimuli, indicative of blindness, was found in 13% of 7-9-week-old males (7/52) and 19% of 21-23-week-old males (9/48), but none of female rats (0/51), which was statistically significant. In addition, the averaged amplitudes of rod- and cone-mediated ERG b-wave responses obtained from males were significantly smaller than the amplitudes of the same responses from age-matched females (-43% and -26%, respectively) at 7-9 weeks of age. There was no difference in the retinal and brain morphology, brainstem auditory responses, or ultrasonic vocalizations between the animals with normal and abnormal ERGs. In summary, male Wistar Han rats had altered retinal responses, including a complete lack of response, when compared with female rats at 7-9 and 21-23 weeks of age. Therefore, sex differences should be considered when using Wistar Han rats in toxicity and safety pharmacology studies with regards to data interpretation of retinal functional assessments.